MULTILEVEL OSTEOSYNTHESIS OF THE LOWER EXTREMITIES BY THE ILIZAROV METHOD TO ELIMINATE DEFORMITIES AND SHORTENINGS IN CHILDREN AND ADOLESCENTS - Jahongirovna Mahlie Jumayeva (International Journal of Business, Law and Political Science, 2024)
This study evaluates the effectiveness of multilevel lower-limb osteosynthesis using the Ilizarov method in correcting deformities and limb shortening in children and adolescents. The technique applies the principles of distraction osteogenesis, allowing precise correction while maintaining joint and soft-tissue function. Patients with congenital deformities, post-traumatic defects, and developmental abnormalities underwent staged correction using circular external fixation. Clinical and radiological assessments were used to monitor alignment, limb length, bone regenerate formation, and functional recovery. Gradual distraction and frame adjustments were continued until optimal correction was achieved. The findings demonstrated substantial improvement in limb alignment, restoration of length, and enhanced mobility. Most patients reached full weight-bearing within standard rehabilitation timelines. Complications such as pin-site infection or delayed consolidation were minimal and effectively managed. Overall, multilevel osteosynthesis with the Ilizarov method provides a reliable and safe approach for treating complex lower-extremity deformities in the pediatric population, offering high corrective accuracy and favorable functional outcomes.